Geographical Forwarding Methods in Vehicular Ad hoc Networks - Kashif Naseer Qureshi; Abdul Hanan Abdullah; Anwar Mirza; Raja Waseem Anwar (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Vehicular ad hoc networks are new and emerging technology and special class of mobile ad hoc networks that provide wireless communication between vehicles without any fixed infrastructure. Geographical routing has appeared as one of the most scalable and competent routing schemes for vehicular networks. A number of strategies have been proposed for forwarding the packets in geographical direction of the destination, where information of direct neighbors is gained through navigational services. Due to dynamically changing topologies and high mobility neighbor information become outdated. To address these common issues in network different types of forwarding strategies have been proposed. In this review paper, we concentrate on beaconless forwarding methods and their forwarding methods in detail.